Performance of Three Genera of Entomopathogenic Fungi as Potential Microbial Control Agents Against the Flea Beetle Phyllotreta Striolata F. (Coleoptera : Chrysomelidae) - Priyatno, Tri Puji (2001)
The striped flea beetle (FB), Phyllotreta striolata F. (Coleoptera: Chrysomelidae), is not only a serious pest of canoia and mustard but also feed on a wide range of other brassicas. Entomopathogenic fungi (EF) are promising agent for biological control of FB and are gaining increasing attention worldwide as mycoinsecticide. The potential of three genera of EF, Metarhizium anisopliae, Beauveria bassiana and Paecilomyces fumosoroseus, has been studied in the laboratory and the field against the striped FB, Phyllotreta strio/ata F. Surveys for FB naturally infected with EF indicated that M anisopliae v. manus and B. bassiana were the potential EF in the populations of FB sampled from vegetable area at UPM's Research Park, Serdang. However, the incidence of infection was very low. Therefore, introduction of virulent isolates into a temporary habitat must be done. Test for pathogenicity of 16 isolates ofEF against adult FB found only one isolate of M anisopliae (MPs) causing mortality in excess of 50%. Four isolates were tested for pathogenicity against the eggs and larvae of the FB. Two isolates of M anisopliae (MPs and Cy3), one B. bassiana (WIs) and one P. fumosoroseus (Pt) were found to be highly pathogenic against the FB larvae while both isolates of M anisopliae were infective against the FB eggs. The resistance of FB adults against EF was caused by the existence of fungistatic compounds on the integument. Five straight chain fatty acids (C4, C6, C7, C8, and C9) suspected as fungistatic compounds based on analysis using Gas Chromatography were proven to inhibit conidial germination. Two media, rice flour and sponge-rice flour medium, examined for conidial massproduction of M anisopliae v. majus and P. fumosoroseus indicated that the spongerice flour medium was shown to be potentially efficient for mass-production of fungal spores.